PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS V SD NEGERI 29 PEKANBARU - Gustri Lestari; Eddy Noviana; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : The research was done because of the low of learning outcomes on civic PKn of 5th students of SD 29 Pekanbaru. It can be seen from the minimum completeness criteria(KKM) from that school is 75. From 37 students who reach KKM was 12 (32,43%) and did not reach the KKM was 25 (67,57) with class avarage was 66,30. The purpose of this research is to improve the learning outcomes on PKn of 5th students of SD Negeri 29 Pekanbaru school year 2017/2018 with as many students 37 that consisting of 23 students and 14 schoolgirls with aplication of learning cycle model. Learning cycle is student centered learning model. That the research is done two cycles. After the research of the learning cycle model. The learning results of students in PKn lesson improved from a basic score of 32,43% with an average score of 66,30 to 48,65% with an avarage score of 72,30% in cycle I, and later improved again and becama 86,49% with average score of 81,22 in cycle II. The percentage of the teacher;s activies have improved well wich can be seen from the improvement of the percentage in cycle I that is 65% to 85% in cycle II. The percentage of student’s activies have improved as well from 60% in cycle I to 85% in cycle II. Based on the explanation abov, it can be concluded that the learning cycle model can improve model can improve the learning results in PKn lesson of the 5th grade students in SD Negeri 29 Pekanbaru.Keywords: Learning Cycle, Learning Outcomes Pkn